Analyzing the Identity Aspect of Cultural Heritage of Isfahan City from the Viewpoint of Visitors With the Aim of City Branding - Zali, Nader; Zamani-Poor, Masoud; Arghash, Amin (Anuário do Instituto de Geociências, 2017)
Using modern strategies and methods in city marketing is one way to attract more resources, and city branding seems as the most important tool in this process. The main purpose of this study is to examine identity aspects of cultural heritage of Isfahan (handicrafts, historical monuments, and lifestyle) - a city that is the symbol of Islamic culture and civilization of Iran- based on city branding criteria (Presence, place, pulse, potential, people, and prerequisite). The study is a field research and is based on data analysis. The result explored that historical monuments in viewpoint of three groups of Isfahan's visitors (residents, domestic and foreign visitors) carry a high international standing, possess the best quality of place, enjoy ample opportunities for city developing, are high in attraction and activities, have high transparency, sociability, and flexibility, also own the best infrastructure for different purposes in compare to the two other aspects of cultural heritage of Isfahan city (handicrafts and lifestyle). In other words, the most distinctive aspect of Isfahan that makes the identity of the cultural heritage is its historical monuments which have the capability to become an international brand.